PERAN KNOWLEDGE SHARING TERHADAP KINERJA UKM BERBASIS SIKAP KEWIRAUSAHAAN - Widodo . (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2013)
This study aims to analyze the role of knowledge sharing lead to improved organizational performance based on the entrepreneurial attitude that includes learning orientation and risk taking. Purposive sampling technique is the number of samples in this study of 135 respondents. Analysis techniques using Structural Equation Model (SEM) with AMOS Soptware. The study results showed that entrepreneurial attitude that includes learning orientation and risk taking to organizational performance through knowledge sharing variables have a higher effect when compared with immediate effect. It shows that the role of knowledge sharing has led to increased organizational performance based on the entrepreneurial attitude that includes learning orientation and risk taking.